Assessment of arterial stiffness via arterial pulse waveform - See, Clement Wei Xian. (2011)
Arterial stiffness is believed to contribute to age-related increases in the incidence of cardiovascular disease (CVD). Therefore, this project aims to study the arterial pulse waveforms between the hypertensive and normotensive subjects of different age groups. In addition, this project attempts to establish normal ranges for various parameters.